A Battery-Powered Tram ready to Operate in Bali; an Answer to Green Energy Public Transportation - I Made Yogi Pramana (Bali Tourism Board, 2021)
In 1945, Indonesia achieved its Independence from Japan. However, starting from 1945 until 2019, the development of the railway system in Indonesia has stagnated. In early 2020, PT KAI announced a new project through their official Instagram account @Keretaapikita. It would be a collaboration project between the KAI, the Central Government and Regional Governments to plan and discuss the development of rail-based urban mass transportation in several big cities in Indonesia, including Bali. It was a part of the Government’s strategy to equalize area development throughout Bali and manifest accessible transportation. Including the supporting plan for North Bali Airport and mass transportation establishment. Over the years, a recent study revealed that the community interest in public transportation had plummeted drastically. However, it was shown that the community showed a strong perception in supporting the development of alternative modes of train/LRT/ART to all districts in Bali. Furthermore, the battery-based electric tram in Bali is scheduled to start its construction in March 2022. The completion would depend on the result of the feasibility study.